(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose – The current research is driven to observe the mediating role of Workplace Spirituality (WPS) on Organizational factors and Organizational Performance among employees across industries. Design/methodology/approach – The data included different level of employees from various industries in India, the researcher has employed structural equation modelling to analyse the collected data. Findings – The present research identifies that Organizational factors such as Organizational Change (OCh), Organisational Culture (OCu), and Organizational Environment (OEn) are the significant predictors of Organizational Performance (OP). This study reveals Workplace Spirituality (WPS) acts as a mediator on Organizational factors and Organizational Performance and the direct association of predictors and criterion variables are stronger than indirect relationship. Originality/value – This study discovers the role of WPS on the relationship between Organizational factors and Organizational Performance. Rarely the empirical research that examines the association of various organisational, personal factors with organizational performance through the behavioural factor Workplace Spirituality. The findings of this study would help the organizations to design their policies that nurtures their employees’ individual and team’s performance.